The Influence of Communication and Work Environment on Job Satisfaction of Employees of the Population and Civil Registration Office of Bima City - muslim halil; Mistar Mistar (Fakultas Ekonomi Universitas Indonesia Timur, 2020)
This study aims to determine the existence of a significant influence between communication and the environment on employee job satisfaction at the Population and Civil Registration Office of Bima City, the type of research used is Associative, this research was conducted at the Population and Civil Registration Office of Bima City, the population used is the number staff in the Population and Civil Registry Office of Bim City, consisting of employees (PNS = 34 and Honorary K-II = 20 people) with a population of 54 people, the sample in this study were 37 people. With a sampling technique (simple random sampling). The communication variable has a tcount of 1.162 <ttable 2.035 and a significance value of 0.254> 0.05 while the work environment variable has a tcount of 6,019> ttable 2,035 and a significance value of 0,000 <0.05. The conclusion of this research is that the work environment variable has a significant effect on employee job satisfaction at the Bima City Population and Civil Registry Office while the communication variable has no positive and significant effect on employee job satisfaction at the Bima City Population and Civil Registry Office. Keywords: Communication, work environment, job satisfaction